Social determinants and their interference in homicide rates in a city in northeastern Brazil - Geziel dos Santos de Sousa; Francismeire Brasileiro Magalhães; Isabelle da Silva Gama; Maria Vilma Neves de Lima; Rosa Lívia Freitas de Almeida; Luiza Jane Eyre de Souza Vieira; José Gomes Bezerra Filho (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: This paper aims to analyze the possible relationship between social determinants and homicide mortality in Fortaleza (CE), Brazil. METHOD: To investigate whether the rate of mortality by homicides is related to social determinants, an ecological study with emphasis on spatial analysis was conducted in the city of Fortaleza. Social, economic, demographic and sanitation data, as well as information regarding years of potential life lost, and Human Development Index were collected. The dependent variable was the rate of homicides in the period 2004 to 2006. In order to verify the relationship between the outcome variable and the predictor variables, we performed a multivariate linear regression model. RESULTS: We found associations between social determinants and the rate of mortality by homicides. Variables related to income and education were proven determinants for mortality. The multiple regression model showed that 51% of homicides in Fortaleza neighborhoods are explained by years of potential life lost, proportion of households with poor housing, average years of schooling, per capita income and percentage of household heads with 15 or more years of study. The coefficients for years of potential life lost and households with poor housing were positive. CONCLUSION: The findings indicate that the mortality by homicide is associated with high levels of poverty and uncontrolled urbanization, which migrates to the peripheries of urban centers.